Accessment of the incidence of intra-operative and post-operative complictions of living donor liver transplantation in both donors and recipients during the icu stay - Mohsen Wafdy Mohammed Ayoob; Mohamed Elshafie; Mostafa Elshazly; Saly Salah Eldeen (Cairo : Mohsen Wafdy Mohammed Ayoob, 2010)
Living donor liver transplantation is now the best solution for patients with end stage liver disease and hepatic malignancy . Many factors can affect the duration of post-operative stay of the patients post-transplant . Assessment of the incidence of intra-operative and post-operative complications of LDLT in both donors and recipients during the ICU stay
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Intra - Operative; Liver Transplantation; Post - Operative Complictions